О природе повышенного алмазоудержания в композите алмаз - сплав WC-Cо, полученного с добавками хромсодержащих соединений - Бондаренко, Н.А.; Олейник, Г.С.; Мечник, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Data on the microstructure of the diamond-hard alloy interaction zone in the composite obtained by a standard technology and a technology in which additives are introduced to the initial mixture of chromium-containing substances are presented. It is concluded that the positive role of the additive in the evaluation of diamond-retention of the composite is determined by the following two main factors: (1) lowering the densification temperature of the composite which prevents the development of the diamond→graphite phase transition; (2) binding of the excessive carbon dissolved in cobalt with the formation of binary carbide.